How do career success criteria shape occupational calling: a multi-wave investigation among undergraduates - Mian Xia; Zhe Zhou; Baoguo Xie; Lina Qin; Jingru Chen (BMC Psychology)
Abstract Background Although much is known about the positive effects of occupational calling on the career development of college students, relatively little is known about the antecedents of their occupational calling. The present aimed to examine how career success criteria predict college students’ occupational calling. Methods This multi-wave study was conducted on 1366 undergraduates. Participants were selected using the convenience sampling technique. The data collection tools included a demographic information form, Career Success Criteria Scale, Spiritual Transcendence Scale, Psychological Needs Satisfaction Scale, and Chinese Calling Scale, all of which were completed online. The data were analyzed using descriptive statistics in SPSS software and path analysis in Mplus software. Results Intrinsic fulfillment criteria were positively related to occupational calling (b = 0.21, SE = 0.03, p < 0.001), whereas external compensation criteria were not related to occupational calling (b = -0.04, SE = 0.02, p = 0.08). The positive relationship between intrinsic fulfillment criteria and occupational calling was mediated by spiritual transcendence (b = 0.05, SE = 0.02, 95% CI = [0.02, 0.08]) and psychological needs satisfaction (b = 0.05, SE = 0.01, 95% CI = [0.03, 0.07]). Conclusion Career success criteria of intrinsic fulfillment criteria have positive effects on college students’ occupational calling. Based on the findings of this study, educators and counselors may leverage these findings to help college students foster their occupational calling that leads to true meaningfulness in work.